2008
DOI: 10.1007/s00442-008-1066-2
|View full text |Cite
|
Sign up to set email alerts
|

The relationships between floral traits and specificity of pollination systems in three Scandinavian plant communities

Abstract: The pollination syndrome hypothesis has provided a major conceptual framework for how plants and pollinators interact. However, the assumption of specialization in pollination systems and the reliability of floral traits in predicting the main pollinators have been questioned recently. In addition, the relationship between ecological and evolutionary specialization in pollination interactions is still poorly understood. We used data of 62 plant species from three communities across southern Norway to test: (1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
153
2
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(167 citation statements)
references
References 28 publications
10
153
2
2
Order By: Relevance
“…Other studies have found that white/yellow flowers are visited by fewer species (i.e. are more specialized), while purple flowers are more generalized in alpine environments (Lazaro et al 2008). With rare species being more purple/blue, our results may then indicate that these rare, purple-flowered species benefit from sharing generalist pollinators with common purple species, despite experiencing high amounts of heterospecific pollen (Sargent & Otto 2006;Spigler & Chang 2008).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Other studies have found that white/yellow flowers are visited by fewer species (i.e. are more specialized), while purple flowers are more generalized in alpine environments (Lazaro et al 2008). With rare species being more purple/blue, our results may then indicate that these rare, purple-flowered species benefit from sharing generalist pollinators with common purple species, despite experiencing high amounts of heterospecific pollen (Sargent & Otto 2006;Spigler & Chang 2008).…”
Section: Discussionmentioning
confidence: 51%
“…Indeed, colour is among the most recognizable signals in the identification of 'pollination syndromes' relating to the perception and preference of pollinators (Faegri & van der Pijl 1979;Gumbert et al 1999;Fenster et al 2004;Lazaro et al 2008). For example, blue is typically associated with bee pollination, while red floral colour is related to hummingbird pollination (Faegri & van der Pijl 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Floral symmetry was classified according to flower characteristics of each species. Species in the Asteraceae that contain both bilateral ray florets and radial disc florets have been assigned to radial species following Hegland & Totland (2005) and Lázaro et al's (2008) classifications. Following Dafni (1994) and Hegland & Totland (2005), the area in one plane of floral visual units of each species was calculated according to the shape of the flower.…”
Section: (A) Study Communitymentioning
confidence: 99%
“…We conducted a redundancy analysis with plant species as samples, percentage of the visits to a particular plant species attributed to each functional group as the response variable and floral symmetry (re-coded into dummy variables) as the explanatory variable. Total visits recorded for each plant species and plant species' abundance were entered as covariables to prevent the possible under-sample effects and the influence of composition of the visitor assemblage (Herrera, C. M. 2005;Lázaro et al 2008). Log ( y þ 1) was used to transform the response variables.…”
Section: (A) Study Communitymentioning
confidence: 99%
See 1 more Smart Citation